Addressing the psychosocial aspects of transition to adult care in patients with cystinosis - Stabouli, Stella; Sommer, Anna; Kraft, Stefanie; Schweer, Katharina; Bethe, Dirk; Bertholet-Thomas, Aurelia; Batte, Suzanne; Ariceta, Gema; Brengmann, Sandra; Bacchetta, Justine; Emma, Francesco; Levtchenko, Elena; et al. (Pediatric nephrology, 2024)
Cystinosis is a rare autosomal-recessive lysosomal storage disease that progressively affects multiple organs beginning with the kidneys. Patients require lifelong multidisciplinary care for the management of kidney disease and progressive extra-renal manifestations, and thus, they are especially fragile and vulnerable during transition from pediatric to adult care. Previous documents have provided guidance to help the medical transition of these highly burdened patients. Patients and their families often experience great psychological distress and face significant social challenges; for these reasons, they often need help from psychologists, social workers, and other psychosocial professionals. Due to the rarity of the disease, most psychosocial professionals have no expertise in this disorder and require advice. To this end, a steering committee (SC) composed of six experts, including pediatric nephrologists, psychologists, and social workers with experience in the care for patients with cystinosis, have identified and addressed seven key questions related to psychosocial challenges of the disease and the burden of treatment. Ten additional international experts (the extended faculty, EF) were invited to answer these questions. Since robust evidence is lacking, as in many rare diseases, conclusions were based on collective agreement between members of the SC and the EF, and the consolidated answers were summarized into expert opinion statements. The present document contains information on the concerns and psychosocial burden of patients with cystinosis and of their caregivers, and provides practical advice for timely and appropriate support to facilitate the transition to adult care.